European public relations research: internationalization, institutionalization and reflection to new professional challenges from a socially oriented perspective - Moreno, Ángeles; Tench, Ralph (Instituto de Investigación en Relaciones Públicas, 2014)
Public relations and communication management research in Europe are going through an excellent phase of scholarly development and impact. This effect is being felt because there is an increasing number of educators and researchers bringing a breadth of qualifications and experience to the research field and consequently providing international prominence and recognition.
Investigación en Relaciones Públicas en Europa: internacionalización, institucionalización y reflexión sobre los nuevos retos profesionales desde una perspectiva de orientación social
Keywords: Relaciones públicas - Europa; Public Relations; Europe